ANTIBACTERIAL AND ANTIBIOFILM ACTIVITY OF MELINJO LEAF WATER EXTRACT AGAINST PSEUDOMONAS AERUGINOSA BACTERIA - Ekajayanti Kining (INDONESIA NATURAL RESEARCH PHARMACEUTICAL JOURNAL, 2022)
Pseudomonas aeruginosa is a multi-drug resistant (MDR) human pathogen and known for their biofilm growth making it difficult to eliminate. This research aims to determine the effectiveness of water extract of melinjo leaf (Gnetum gnemon L) on inhibition of cell attachment, growth and degradation of the biofilm using Crystal Violet (CV) biofilm Assay. Reasearch results showed that water extract of melinjo leaf (Gnetum gnemon L) contains saponin, alkaloid, tanin dan steroidal that showed antibacterial activity and antibiofilm against P. aeruginosa. Addition extract can inhibit the attachment cell of 49,80% with a concentration of 25%, temperature of 37,5 oC and the contact time of 45 minutes. With a concentration of 25% (v/v), temperature of 50 °C and the contact time of 3 days, extract of melinjo leaves can inhibit the growth of biofilms of 43,09% and able to degrade the biofilm 43.04% with a concentration of 25% (v/v), temperature 37.5°C and contact time 45 minutes